Cooperative model, digital game, and augmented reality-based learning to enhance students' critical thinking skills and learning motivation - Iqbal A. Rizki; Nadi Suprapto; Hanandita V. Saphira; Yusril Alfarizy; Riski Ramadani; Aulia D. Saputri; Dewi Suryani (Journal of Pedagogical Research, 2024)
Low levels of critical thinking skills and learning motivation, particularly in physics learning, pose significant challenges that must be promptly addressed to ensure students' future success. To tackle this issue, the present study endeavors to develop a Cooperative Model, Digital Game, and Augmented Reality (CAP)-based learning, which is both valid and practical, to enhance these crucial aspects effectively. This study used Educational Design Research through a non-equivalent control group design in the data collection process. Using purposive sampling method, 54 high school students were divided into two classes were involved. The data collection period was from July to August 2022. The research instruments used include syllabus, lesson plan, Adventuring Physics media, critical thinking test instrument, motivation questionnaire, student response questionnaire, validation questionnaire, and observation sheet. Statistical tests used include descriptive, paired, and independent t-tests. The results reveal that the learning products and instruments exhibit strong validity and reliability, alongside a high degree of practicality in their implementation. The experimental group demonstrated a notable improvement both in critical thinking skills and learning motivation. Additionally, students' feedback regarding this learning approach has been overwhelmingly positive. Consequently, this research highlights the importance of fostering more engaging and enjoyable innovations through digital learning in physics education to achieve optimal learning outcomes and enhance 21st-century skills.